Efficacy of a New Cream Formulation of Mupirocin: Comparison with Oral and Topical Agents in Experimental Skin Infections - Gisby, John (American Society for Microbiology, 2000)
A new cream formulation of mupirocin developed to improve patient compliance was compared with systemic and topical antibiotics commonly used to treat primary and secondary skin infections. A mouse surgical wound model infected with Staphylococcus aureus or Streptococcus pyogenes was used. Topical treatment was applied at 4 and 10 h postinfection or oral treatment at a clinically relevant dose was administered 4, 8, and 12 h postinfection; treatments were continued three times daily for a further 3 days. Mupirocin cream was significantly more effective than (P < 0.01; two of eight studies) or not significantly different from (six of eight studies) mupirocin ointment in reducing bacterial numbers. Mupirocin cream was similar in efficacy to oral flucloxacillin but significantly more effective (P < 0.001) than oral erythromycin. It was also similar in efficacy to cephalexin against S. pyogenes but superior against S. aureus (P < 0.01). Mupirocin cream had a similar efficacy to fusidic acid cream against S. aureus but was significantly superior against S. pyogenes (P < 0.01). A hamster impetigo model infected with S. aureus was also used. Topical or oral treatment was administered at 24 and 30 h postinfection (also 36 h postinfection for oral therapy) and then three times daily for a further 2 days. On day 5, mupirocin cream was significantly more effective than mupirocin ointment in one study (P < 0.01) and of similar efficacy in the other two studies. Mupirocin cream was not significantly different from fusidic acid cream or neomycin-bacitracin cream, but it was significantly superior (P < 0.01) to oral erythromycin and cephalexin. Mupirocin cream was as effective as, or superior to, oral and other topical agents commonly used for skin infections.